STRUCTURE AND MECHANICAL PROPERTIES’ RESEARCH OF A500C-CLASS REINFORCEMENT BARS - A. M. Yaznevich (Наука и техника)
Structural and mechanical properties of A500C-class reinforcement bars are investigated in the paper. The paper demonstrates that rolled products of thermally strengthened reinforcement have a layered structure with coaxially located layers having different mechanical characteristics. Micro-hardness measurements have shown that the maximum hardness has a pre-surface part of a reinforcement bar, and the minimum hardness is in the central part. Thickness of the strengthened surface layers grows while increasing a diameter and at preservation of structural composition.